Islamic Values in the United States : A Comparative Study - Haddad, Yvonne Yazbeck, 1935- and Lummis, Adair T. (New York Oxford University Press, 1987)
Islam is now an American phenomenon. This ethnography of immigrant Muslims considers five communities in detail, and provides a highly personalized look at what it means to be a practising Muslim in the USA today.
Include Tables, Bibliography and Index
Keywords: United States -- United States -- Religious life and Customs -- Muslims -- United States